2006
DOI: 10.1093/jac/dkl261
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of penicillin and telithromycin on the expression of Streptococcus pneumoniae capsule

Abstract: Objective: To evaluate the effects of subinhibitory concentrations of penicillin and telithromycin on capsular formation by Streptococcus pneumoniae.Methods: A total of 60 isolates of S. pneumoniae, 20 susceptible, 20 intermediately resistant and 20 resistant to penicillin, were studied. All isolates were susceptible to telithromycin.Results: All isolates were capsulate when grown without antibiotics. Encapsulation was lower after incubation with telithromycin as compared with penicillin in isolates susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Tateda et al (14) reported that azithromycin (AZM) interferes with autoinducer synthesis of Pseudomonas aeruginosa, leading to a reduction of virulence factor production. Subinhibitory concentrations of telithromycin were shown previously to suppress the capsular formation of Streptococcus pneumoniae (15). On the basis of that previous study, we speculated that macrolides may inhibit the virulence of C. gattii, particularly with respect to reduction of the polysaccharide capsule, and may be responsible for an altered innate immune response, especially that involving neutrophils and macrophages, which is consistent with effective host protection.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Tateda et al (14) reported that azithromycin (AZM) interferes with autoinducer synthesis of Pseudomonas aeruginosa, leading to a reduction of virulence factor production. Subinhibitory concentrations of telithromycin were shown previously to suppress the capsular formation of Streptococcus pneumoniae (15). On the basis of that previous study, we speculated that macrolides may inhibit the virulence of C. gattii, particularly with respect to reduction of the polysaccharide capsule, and may be responsible for an altered innate immune response, especially that involving neutrophils and macrophages, which is consistent with effective host protection.…”
supporting
confidence: 51%
“…Macrolide exposure significantly reduced the capsule thickness of highly virulent C. gattii, and the amount of CPS was similarly reduced. Previous studies showed that bacteriostatic antibiotics, such as macrolides and clindamycin, reduce capsule size in S. pneumoniae by inhibiting protein synthesis (15). Furthermore, several previous studies demonstrated the effects of inhibiting macrolide-mediated bacterial virulence, especially in P. aeruginosa (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 fimbriae are known to be critical in internalization and IBC formation ( 58 60 ); their expression in response to ciprofloxacin and subsequent chronic infection development is likely paramount. Although changes in type 1 fimbria transcript abundance was not observed, posttranscriptional modification or capsule downregulation and enhanced FimH exposure might contribute to the observed changes in antibiotic-induced hemagglutination ( 61 , 62 ). Increased numbers of IBCs are associated with an increased risk of chronic cystitis ( 36 ).…”
Section: Discussionmentioning
confidence: 87%
“…20 For example, antibiotics acting on bacterial cell walls can inhibit the synthesis of capsular polysaccharides in Streptococcus pneumoniae. 21 In the study by Nomura et al, it was found that after the treatment of K. pneumoniae with different drugs in 1/4MIC, penicillins, cephalosporins and monoamides could significantly reduce the capsular thickness, quinolones had little effect on the capsular thickness, while aminoglycosides, macrolides and carbapenems showed no significant change in the capsular thickness. 22 Since the mid-1980s, hvKp, which is usually presented as an HMV phenotype, has become a clinically important pathogen and often causes severe disseminated infections.…”
Section: Discussionmentioning
confidence: 98%